Dose‐Dependent Therapeutic Distinction between Active and Passive Targeting Revealed Using Transferrin‐Coated PGMA Nanoparticles. Issue 3 (30th November 2015) - Singh, Ruhani; Norret, Marck; House, Michael J.; Galabura, Yuriy; Bradshaw, Michael; Ho, Diwei; Woodward, Robert C.; Pierre, Timothy G. St.; Luzinov, Igor; Smith, Nicole M.; Lim, Lee Yong; Iyer, Killugudi Swaminathan
Abstract : The paradigm of using nanoparticle‐based formulations for drug delivery relies on their enhanced passive accumulation in the tumor interstitium. Nanoparticles with active targeting capabilities attempt to further enhance specific delivery of drugs to the tumors via interaction with overexpressed cellular receptors. Consequently, it is widely accepted that drug delivery using actively targeted nanoparticles maximizes the therapeutic benefit and minimizes the off‐target effects. However, the process of nanoparticle mediated active targeting initially relies on their passive accumulation in tumors. In this article, it is demonstrated that these two tumor‐targeted drug delivery mechanisms are interrelated and dosage dependent. It is reported that at lower doses, actively targeted nanoparticles have distinctly higher efficacy in tumor inhibition than their passively targeted counterparts. However, the enhanced permeability and retention effect of the tumor tissue becomes the dominant factor influencing the efficacy of both passively and actively targeted nanoparticles when they are administered at higher doses. Importantly, it is demonstrated that dosage is a pivotal parameter that needs to be taken into account in the assessment of nanoparticle mediated targeted drug delivery. Abstract : Multimodal polymeric nanoparticles for active and passive targeted therapy are prepared and administered in vivo in an orthotopic PC3 prostate cancer mouse model. A dose‐dependent distinction in efficacy between the formulations is demonstrated using in vivo bioluminescence imaging and monitoring the effect of treatment on animal weights. Actively targeted nanoparticles are more efficacious at a lower dose; however, at higher doses the two formulations become therapeutically indistinguishable.